1996
DOI: 10.1002/j.1460-2075.1996.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

A new stress protein: synthesis of Schizosaccharomyces pombe UDP-Glc:glycoprotein glucosyltransferase mRNA is induced by stress conditions but the enzyme is not essential for cell viability.

Abstract: We have identified and begun the characterization of the gene encoding UDP‐Glc:glycoprotein glucosyltransferase in Schizosaccharomyces pombe. This gene, here designated gpt1, codes for a polypeptide having a signal peptide of 18 amino acids followed by 1429 amino acids with no transmembrane domain, as expected for a soluble protein of the endoplasmic reticulum (ER). The C‐terminal tetrapeptide PDEL most probably corresponds to a novel ER retention signal in this fission yeast. Synthesis of the corresponding mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 38 publications
6
73
1
Order By: Relevance
“…We postulate that the principal role of transcriptional up-regulation of uda-1 is to increase the availability of UDP-glucose in the lumen of the ER or pre-GA (see below) under conditions of ER stress, thereby increasing the glucosylation of improperly folded proteins. Up-regulation of GT transcription under ER stress has been reported previously in S. pombe (46) and human cells (47) and seems to occur together with that of UDA-1 (Fig. 8).…”
Section: Discussionsupporting
confidence: 78%
“…We postulate that the principal role of transcriptional up-regulation of uda-1 is to increase the availability of UDP-glucose in the lumen of the ER or pre-GA (see below) under conditions of ER stress, thereby increasing the glucosylation of improperly folded proteins. Up-regulation of GT transcription under ER stress has been reported previously in S. pombe (46) and human cells (47) and seems to occur together with that of UDA-1 (Fig. 8).…”
Section: Discussionsupporting
confidence: 78%
“…This reaction is not essential for cell viability under normal growth conditions (31). Moreover, complete or severe reduction in monoglucosylated glycan formation caused by disruption of glucosidase II subunit ␣-or ␤-or GT-encoding genes did not affect cell growth or morphology.…”
Section: Analysis Of S Pombementioning
confidence: 88%
“…Since catalysis of glucose transfer by UGTR is a Ca 2ϩ -dependent process (49) it has been suggested that hydrolysis of UDP-glucose, which is coupled to glucose transfer, may provide the energy necessary for dissociating bound glycoproteins from UGTR (8). We have been unable to demonstrate transfer of glucose to oligosaccharides of null(Hong Kong) during Ca 2ϩ -dependent dissociation of UGTR, but this may reflect poor detection limits associated with our analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Reglucosylation of high mannose-type glycans has been detected in microsomal preparations from mammals, plants, fungi, yeast, and protozoa (7,8) and is catalyzed by the ER resident protein UDP-glucose:glycoprotein glucosyltransferase (UGTR) (8 -10). Importantly, only high mannose-type oligosaccharides attached to unfolded proteins function as acceptors in the glucose transfer reaction (11)(12)(13).…”
mentioning
confidence: 99%